The role of CaMKII regulation of phospholamban activity in heart disease - Mattiazzi, Alicia; Kranias, Evangelia (Frontiers in Pharmacology, 2014)
Phospholamban (PLN) is a phosphoprotein in cardiac sarcoplasmic reticulum (SR) that is a reversible regulator of the Ca2+-ATPase (SERCA2a) activity and cardiac contractility. Dephosphorylated PLN inhibits SERCA2a and PLN phosphorylation, at either Ser16 by PKA or Thr17 by Ca2+-calmodulin-dependent protein kinase (CaMKII), reverses this inhibition. Through this mechanism, PLN is a key modulator of SR Ca2+ uptake, Ca2+ load, contractility and relaxation. PLN phosphorylation is also the main determinant of β1-adrenergic responses in the heart. Although phosphorylation of Thr17 by CaMKII contributes to this effect, its role is subordinate to the PKA-dependent increase in cytosolic Ca2+, necessary to activate CaMKII. Furthermore, the effects of PLN and its phosphorylation on cardiac function are subject to additional regulation by its interacting partners, the anti-apoptotic HAX-1 protein and Gm or the anchoring unit of protein phosphatase 1. Regulation of PLN activity by this multimeric complex becomes even more important in pathological conditions, characterized by aberrant Ca2+-cycling. In this scenario, CaMKII-dependent PLN phosphorylation has been associated with protective effects in both acidosis and ischemia/reperfusion. However, the beneficial effects of increasing SR Ca2+ uptake through PLN phosphorylation may be lost or even become deleterious, when these occur in association with alterations in SR Ca2+ leak. Moreover, a major characteristic in human and experimental heart failure is depressed SR Ca2+ uptake, associated with decreased SERCA2a levels and dephosphorylation of PLN, leading to decreased SR Ca2+ load and impaired contractility. Thus, the strategy of altering SERCA2a and/or PLN levels or activity to restore perturbed SR Ca2+ uptake is a potential therapeutic tool for heart failure treatment. We will review here the role of CaMKII-dependent phosphorylation of PLN at Thr17 on cardiac function under physiological and pathological conditions.